A Framework for Computing-Independent Models: Transformation Rules and MVC Architecture - models, Abstract—This paper presents a model-oriented development approach to software development in the Model-View-Controller (MVC) architectural standard. This approach aims to expose a process of extractions of information from the; work, in which through rules; syntax defined in this; language, assists in the design of the initial model; its future conversions. The proposed paper presents a syntax based on the natural; language, according to the rules agreed in the classic grammar of the Portuguese; MOF., added to the rules of conversions generating models that follow the norms of the Object Management Group (OMG); the Meta-Object Facility (Journal of Computer Engineering, 2019)
—This paper presents a model-oriented development approach to software development in the Model-View-Controller (MVC) architectural standard. This approach aims to expose a process of extractions of information from the models, in which through rules and syntax defined in this work, assists in the design of the initial model and its future conversions. The proposed paper presents a syntax based on the natural language, according to the rules agreed in the classic grammar of the Portuguese language, added to the rules of conversions generating models that follow the norms of the Object Management Group (OMG) and the Meta-Object Facility MOF